The role of brain biopsy in the clinical management of HIV‐related focal brain lesions. Issue 10 (13th July 2018) - Acosta, MC; Kundro, M; Viloria, G; Peressín Paz, A; Morello, F; Latorre, F; Seoane, E; Toibaro, J; Losso, M
Abstract : Objectives: Up to 20% of HIV‐related focal brain lesion (FBL) diagnoses cannot be determined without invasive procedures. In such cases, brain biopsy is an important step in the evaluation algorithm. The aims of this study were to describe the clinical outcomes of patients with FBL, the proportion of diagnoses confirmed by brain biopsies and their aetiologies, and to analyse the proportion of patients in whom the biopsy motivated a change in therapeutic management. Methods: A retrospective cohort study was performed. The data from clinical records of patients with HIV‐related FBL admitted between January 2005 and December 2015 were reviewed. Results: A total of 137 patients were included in the study. The median age was 39 years [interquartile range (IQR) 33–44.5 years]. The median CD4 count was 54 cells/μL (IQR 21–124 cells/μL). Cerebral brain biopsy was performed in 21.16% of patients (29 of 137); 68.9% of these individuals (20 of 29) were diagnosed by histology, with results of central nervous system (CNS) lymphoma in 20.6% (six of 29), progressive multifocal leucoencephalopathy in 6.8% (two of 29), toxoplasmosis in 6.8% (two of 29), tuberculoma in 6.8% (two of 29), and other diagnoses in 27.6% (eight of 29). In nine patients, the histology was nonspecific. In 75.8% of patients (22 of 29), the result of the biopsy led to a change in the therapeutic management. We did not observe higher rates of mortality related to the procedure. Overall mortality at 30 and 90 days was similar in patients who were and were not biopsied. Conclusions: In this retrospective cohort study, cerebral biopsy was associated with significant adjustments in therapeutic management for a high percentage of patients.